PERUBAHAN MAKNA KATA PADA BAHASA GAUL GENERASI Z DI MEDIA SOSIAL - M.Taufan Pasya Lubis; Habibi Hutabarat; Rizkan El Fattah; Erli Diansyah; Dila Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of digital technology has influenced various aspects of life, including language styles among the younger generation. As active users of social media platforms like TikTok, Instagram, and Twitter, Generation Z often creates new forms of language that have undergone changes in meaning from their original meanings. This study aims to describe the forms of changes in the meaning of words in slang used by Generation Z on social media and analyze the factors causing these changes. Words such as "gas," "bestie," "flexing," and "healing" have experienced shifts in function and meaning in everyday contexts. The conclusions of this study confirm that Generation Z slang reflects the social and cultural dynamics of the digital era and demonstrates that social media plays a significant role in shaping and disseminating changes in meaning in modern Indonesian.